Analysis Of The Marketing Channel Efficiency Of Fresh Fruit Bunches (FFB) Among Smallholder Farmers In Gunung Ambat Village, Sei Bingai District, Langkat Regency - Yudha Nugraha Pane; Tifany Zia Aznur (International Journal of Health Engineering and Technology, 2026)
This study aimed to analyze the marketing channels of fresh fruit bunches (FFB) of oil palm (Elaeis guineensis Jacq.) in Gunung Ambat Village, Sei Bingai District, Langkat Regency, and analyze the marketing efficiency of fresh fruit bunches (FFB) of oil palm in Gunung Ambat Village, Sei Bingai District, Langkat Regency. The research was conducted in Gunung Ambat Village using a purposive method for site selection. A total of 42 oil palm farmers were selected as respondents using the simple random sampling method. The data were analyzed using descriptive and quantitative approaches, including marketing channel analysis, marketing margin, Farmer’s Share, marketing efficiency, and the cost-benefit ratio. The results showed that there were two marketing channels, namely Channel I (Farmers → Collecting Traders → PT Putra Grup Agribisnis) and Channel II (Farmers → PT Putra Grup Agribisnis). A total of 32 farmers (76.19%) used Channel I, while 10 farmers (23.81%) used Channel II. The marketing margin in Channel I was IDR 200/kg, whereas Channel II had a marketing margin of IDR 0/kg. The Farmer’s Share values were 93.33% for Channel I and 100% for Channel II. The marketing efficiency values were 4.17% for Channel I and 3.00% for Channel II, indicating that both channels were efficient because their efficiency values were below 50%. The cost-benefit ratio in Channel I was 0.60, whereas the ratio for Channel II was not calculated because farmers sold FFB directly to PT Putra Grup Agribisnis without any marketing intermediary. Based on the overall analysis, Channel II was found to be the more efficient marketing channel due to its shorter marketing chain, lower marketing margin, and higher Farmer’s Share.